Reply to Yu and Zenker - Freeman, James B. (Informal Logic)

(untitled) (Informal Logic, 2024)
Yu and Zenker (2022) argue that the oft-made distinction between convergent and linked argument structure is problematic. If their account holds, the linked/convergent distinction, at least as I have characterized it (Freeman 2011), seems to violate the dictum that structural analysis should come before evaluation. In this Reply I defend the position that we do not need to estimate or determine argument strength to determine whether the premises of an argument are linked or convergent.